Understanding perspectives of college going youths: insights into social behavior and reproductive health needs - Walia, Dinesh K.; Kumar, Anuj; Vashisht, Pooja; Bakshi, Ravleen K.; Walia, Meghna (International Journal Of Community Medicine And Public Health, 2025)
Background: College-going youth face significant psychological and reproductive health challenges due to academic pressures, social relationships, and personal development. Social support, including counseling, is essential in addressing these concerns. The objectives were to examine the social restrictions and reactions to family conflicts among college going youths and to explore the perceived benefits, barriers and perceptions related to social behavior and reproductive health needs of youths. Methods: A cross sectional study was done among 265 college going youth aged 17-30 years who were selected by convenience sampling. Their psychosocial stressors and accessibility to reproductive health information were explored. Results: The study involved 265 participants’ majority of whom (76.6%) faced social restrictions, and 68.3% reacted, mostly by understanding their parents' views (75.1%). Family conflicts were reported by 15.1%. Major barriers to seek counseling for psychological stressors included fear of judgment (54.3%) and being labeled as a mental health sufferer (23.8%). Despite 55.8% recognizing counseling benefits, access to mental health support was inconsistent, with only 37% having access to counselors. Internet (53.2%) was the primary source for reproductive health information and 43% of the participants agreed that counseling improves reproductive health status. Conclusions: Addressing social and reproductive health issues requires an understanding of perceptions and needs of youths providing them trustworthy information and support system. Efforts should be made to establish supportive settings at college levels for reducing barriers in communication to improve their social behavior and reproductive health.